Psychotic-like experiences and adverse life events in young people. Does gender matter? - Adjorlolo, S.; Awortwe, V.; Anum, A.; Huang, K.Y.; Mamah, D. (Child and Adolescent Mental Health, 2023)
Background: Psychotic-like experiences (PLEs) and adverse life events (ALEs) are highly prevalent in sub Saharan Africa where gendered practices are also common. There is, however, a paucity of data on how the relationship between PLEs and life adversities is influenced by gender. The current study addressed this gap. Method: Data were collected from 1886 school-based young people (1174 females) in Ghana, West Africa using a cross-sectional survey methodology and analyzed using Chi-square, independent t-test, Pearson corre lation, and multivariate regression. Results: The results showed that victimization experiences, school stress and having a family member with mental illness were significantly associated with PLEs in both males and females. In contrast, substance misuse and experiences of head trauma correlated significantly with PLEs in females only. Conclusion: Life adversities constitute major risk factors for PLEs among school-based young people in Ghana, who could benefit from gender neutral and gender-sensitive intervention programming to remediate the effects of life adversities on PLEs.
Research Article
Keywords: Adolescents; adverse life experiences; psychosis; Africa; Ghana